Language Delay in Duchenne’s Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs, 2007)
Developmental milestones of 130 male children with Duchenne’s muscular dystrophy (DMD) and their 59 unaffected siblings were determined by retrospective parental reports and compared by researchers at the City University and Columbia University, New York, NY; and Scottish Rite Children’s Medical Center, Atlanta, GA.